Resistance and Solidarity against Domestic Violence in Children’s Novel Lola Rose (2003) by Jacqueline Wilson - Toh, Haw Ching Florence; Liau, Wei Agnes (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Dame Jacqueline Wilson is a former Children’s Laureate (2005 - 2007) with more than 100 contemporary realistic children’s novels which have been translated into over 30 languages. Drawing from her childhood experiences, Wilson’s works highlight “subjects once seldom discussed in literature aimed at the young but with which children themselves may be familiar either from their own lives or through observing others in the classroom or playground” (Tucker & Gamble, 2001, p. 72). The issues discussed are “seen through the eyes of children who survive, observing and adapting to their complicated lives” (Eccleshare, 2003, para. 1). Despite that, there remains a scarcity in the scholarship devoted to serious analyses of her novels (Armitstead, 2004; Corbett, 2007; Duncan, 2009). The paper responds to this gap by focusing on Wilson’s Lola Rose (2003) with particular attention given to the theme of domestic violence encountered by Lola Rose, the pre-adolescent girl protagonist.